Paradigm Shift in the Implementation of the Law of the Sea in Indonesia - Purwaka, Tommy Hendra (UI Scholars Hub, 2021)
Indonesia has experienced four times paradigm shift in the implementation of the law of the sea since it declared its archipelagic state principle in 1957 through the 1957 Djuanda declaration up to now. The shifting of paradigms can be viewed as a progressive development on the implementation of the law of the sea in Indonesia. The first paradigm was ocean space paradigm which was clearly shown in the 1957 Djuanda declaration and along the way of the diplomacy efforts of Indonesia in the first (1958), the second (1960) and the third (1982) UNCLOS. The first paradigm showed how Indonesian people viewed ocean space of Indonesian archipelago as an integral part of national territory of Indonesia. The ocean space of Indonesian archipelago, however, should be filled with development activities as the implementation of the law of the sea. This has raised ocean development paradigm in 1985 as the second paradigm. Problems and constraints of ocean development faced by government of Indonesia which consists of central government, provincial government, regency government and municipal government have led to the maritime continent paradigm as the third paradigm in 1990s. The third paradigm viewed the ocean and land space of Indonesian archipelago as a continent. By thinking so, maritime jurisdictional problems raised by the involvement of central, provincial, regency and municipal governments in Indonesia’s ocean development will be able to be solved. As a matter of fact, the appearance of the third paradigm has complicated efforts of government in socializing the implementation of the law of the sea to all government levels and to Indonesian people. For this reason, government of Indonesia in the year of 2000 formulated national ocean policy. This policy combined ocean space, ocean development and maritime continent paradigms which can be viewed as the fourth paradigm. The fourth paradigm then can be named as ocean policy paradigm.